Internalisasi Nilai Pendidikan Islam di SMK Negeri Tembarak - Sakdiyyah, Siti Chalimatus (Jurnal Ilmiah Citra Ilmu, 2021)
Every school certainly has a culture, including SMK Negeri Tembarak. In its implementation, the school culture at SMK Negeri Tembarak is internalized by the value of Islamic education because the value of Islamic education is not maximally absorbed, resulting in negative behavior even though there is a school culture at SMK Negeri Tembarak. This type of research is a field research with qualitative methods. Data collection techniques are observation, interviews, and documentation. And data analysis techniques with data editor, data display, and data verification. The results of this study are first, the process of school culture in internalizing the value of Islamic education at SMK Negeri Tembarak is inseparable from the principal's program and the school's annual program, reinforced by the presence of supporting facilities such as musola, extracurricular, intracurricular, and others. Second, the form of implementation of the existing school culture that supports Islamic Education teachers in internalizing the values ​​of Islamic education implies moral values, worship values, and Islamic values. Third, the supporting and inhibiting factors. The supporting factors are active students, environment, habits, the existence of uswah or examples, and interesting activities. While the obstacles in the form of apathy, less attractive activities, lack of socialization, environment, and new habits.